Soy Intake and Risk of Type 2 Diabetes Among Japanese Men and Women: JACC Study - Yan, Fangyu; Eshak, Ehab S.; Shirai, Kokoro; Dong, Jia-Yi; Muraki, Isao; Tamakoshi, Akiko; Iso, Hiroyasu (Frontiers in Nutrition, 2022)
Abstract The evidence on the protective effects of soy foods against type 2 diabetes has been inconsistent. We thought to examine the association between the dietary intakes of soy and the risk of diabetes in a prospective study encompassing 21,925 healthy Japanese men and women aged 40-79 years. A validated self-administered food frequency questionnaire determined the intakes of soy, and their associations with risk of type 2 diabetes were evaluated by the logistic regression analysis. During the 5-year follow-up period, we observed 593 new cases of type 2 diabetes (302 in men and 291 in women). There was no association between dietary intakes of soy foods and the risk of type 2 diabetes among men. Whereas, among women, higher tofu intake was inversely associated with risk of type 2 diabetes; the multivariable odds ratios (ORs) of type 2 diabetes were 0.92 (95% CI: 0.69-1.21) for 3-4 times per week and 0.67 (95% CI:0.49-0.94) for almost daily (p-trend = 0.03) in reference to those consuming tofu less than 3 times per week. Intakes of boiled beans and miso soup were not associated with the risk in both genders. The inverse association tended to be more evident among overweight women and post menopaused women. In conclusion, the frequency of tofu intake was inversely associated with the risk of type 2 diabetes among women.